2015
DOI: 10.3109/13561820.2014.1003635
|View full text |Cite
|
Sign up to set email alerts
|

Developing health and social care planning in collaboration

Abstract: Collaboration between different professions in community care for older people is often both difficult and complex. In this project, a participatory action research (PAR) was conducted in order to support the professions involved in the care for older people to develop individualized health and social care plans. Cases from daily work were discussed in different professional groups over a period of one year. A key finding was that lack of knowledge regarding the other professions' field of expertise and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…The findings show that not all care‐planning conferences conducted have a clear purpose or follow a structured agenda to ensure that all the different parts are included. They also confirm the complexity when different actors are collaborating, as revealed in other studies (Jansen et al., ; Rämgård et al., ). In Sweden, the law (SOU, :20) regulates care‐planning collaboration.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings show that not all care‐planning conferences conducted have a clear purpose or follow a structured agenda to ensure that all the different parts are included. They also confirm the complexity when different actors are collaborating, as revealed in other studies (Jansen et al., ; Rämgård et al., ). In Sweden, the law (SOU, :20) regulates care‐planning collaboration.…”
Section: Discussionsupporting
confidence: 86%
“…Organizations and professions have their own legislations, values, responsibilities and budgets, and with this system, there is a risk of fragmentation and lack of continuity of the care provided (Berglund, Hasson, Kjellgren, & Wilhelmson, ; Sundström, Petersson, Rämgård, Varland, & Blomqvist, ). Collaboration among different professions in the community is complex and multifaceted (Rämgård, Blomqvist, & Petersson, ), and studies have identified various barriers and facilitators related to the organization of health care (Jansen, Heijmans, & Rijken, ).…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative inter-professional routines develop slowly and require individual, practice and system support (Rämgård et al 2015). Our data showed how preoccupation with financial viability at two new GPSCs could conflict with other objectives, significantly slowing development of collaborative routines for chronic care.…”
Section: Discussionmentioning
confidence: 95%
“…International experiences indicate that practice transformation towards multidisciplinary care takes time, as clinicians and other practice staff adjust established practices and routines (Rämgård et al 2015). Success requires: embedding principles of evidencebased care, relational continuity and patient-centred care; systematic approaches to delivery of comprehensive clinical care (Wagner et al 2012); and active, visible leaders, explicit staff training and quality data (Quinn et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Health and social care needs of older persons with multiple diseases are often extensive, complex and changing over time . Several different occupations are involved in the care, but the collaboration is not unproblematic . As care of older persons is increasingly provided outside hospitals and nursing homes, the interfaces between health and social care as well as between primary and community care have become an obstacle for an integrated care that fulfils the needs of older persons at home .…”
Section: Introductionmentioning
confidence: 99%